Books
in black and white
Main menu
Share a book About us Home
Books
Biology Business Chemistry Computers Culture Economics Fiction Games Guide History Management Mathematical Medicine Mental Fitnes Physics Psychology Scince Sport Technics
Ads

Elementary Differential Equations and Boundary Value Problems - Boyce W.E.

Boyce W.E. Elementary Differential Equations and Boundary Value Problems - John Wiley & Sons, 2001. - 1310 p.
Download (direct link): elementarydifferentialequations2001.pdf
Previous << 1 .. 489 490 491 492 493 494 < 495 > 496 497 498 499 500 501 .. 609 >> Next

400 'V e-(2n-1) 2n2a2t/400 (2n-1) nx
---------------sin------------
400
u(x,t) = ----------
rr
n 2n1 2 0
n=1
18b. For aluminum, we have a2 = .86 cm2/sec (from Table 10.5.1) and thus the first two terms give
u(10,30) = 400 [e-n2 (.86) 30/400 1 e-9n2 (.86) 30/400 }
, n 3
= 67.228oC. If an additional term is used, the temperature is increased by
e-25n2 (.86) 30/400 = 3 x 10-6 degrees C. n
19b. Using only one term in the series for u(x,t), we must solve the equation 5 = (400/n)exp[-n2(.86)t/400] for t. Taking the logarithm of both sides and solving for t yields t = 400ln(80/n)/n2(.86) = 152.56 sec.
20. Applying the chain rule to partial differentiation of u with respect to x we see that ux = u^?x = u^(l/L) and uxx = u^(l/L)2. Substituting u^/L2 for uxx in the heat
equation gives a 2u^/L2 = ut or u^ = (L2/a 2)ut. In a
L2
2 2 L similar manner, ut = uTTt = uT(a /L ) and hence -ut = uT
a2
and thus u^ = uT.
22. Substituting u(x,y,t) = X(x)Y(y)T(t) in the P.D.E. yields a2 (X"YT + XY"T) = XYT', which is equivalent to X" Y" T'
+ = --------. By keeping the independent variables x
X Y a 2T
and y fixed and varying t we see that T'/a2T must equal some constant o1 since the left side of the equation is fixed. Hence, x"/x + y"/y = T'/a 2T = o1, or X"/X = o1 - Y"/Y and T' - o1a 2T = 0. By keeping x fixed and varying y in the equation involving X and Y we see that o1 - Y"/Y must equal some constant o2 since the left side of the equation is fixed. Hence,
X"/X = o1 - Y"/Y = o2 so X" - o2X = 0 and Y" -(o1 - o2)Y = 0. For T' - o1a2T = 0 to have solutions that remain bounded as t ^ ro we must have G1 < 0. Thus, setting o1 = -X2, we have T' + a2X2T = 0. For X" - a2X = 0 and homogeneous B.C., we conclude, as in Sect. 10.1, that o2 < 0 and, if we let
Section 10.6
221
2 //2
02 = - , then X + X = 0. With these choices for a1 and 02
we then have Y" + (X 2-^2)Y = 0.
Section 10.6, Page 588
3. The steady-state temperature distribution v(x) must satisfy Eq.(9) and also satsify the B.C. vx(0) = 0, v(L) = 0. The general solution of v" = 0 is v(x) = Ax + B. The B.C. vx(0) = 0 implies A = 0 and then
v(L) = 0 implies B = 0, so the steady state solution is
v(x) = 0.
7. Again, v(x) must satisfy v" = 0, v'(0) -v(0) = 0 and v(L) = T.
The general solution of v" = 0 is v(x) = ax + b, so v(0) = b,
v'(0) = a and v(L) = T. Thus a - b = 0 and aL + b = T, which
give a = b = T/(1+L). Hence v(x) = T(x+1)/(L+1).
9a. Since the B.C. are not homogeneous, we must first find
the steady state solution. Using Eqs.(9) and (10) we have v" = 0 with v(0) = 0 and v(20) = 60, which has the
solution v(x) = 3x. Thus the transient solution w(x,t) satisfies the equations a 2wxx = wt, w(0,t) = 0, w(20,t) = 0 and w(x,0) = 25 - 3x, which are obtained from Eqs.(13) to (15). The solution of this problem is given by Eq.(4) with the cn given by Eq.(6):
(7 0cosnn+5 0)/nn, and thus
u(x,t) = 3x + ^
70cosnn + 50
-0.86n2n2t/400-
nnx
e
since
20
n=1
a2 = .86 for aluminum.
9b.
9c.
M u
9d. Using just the first term of
of the sum, we have n
_n = 15 .15. Thus
4
222
Section 10.6
---e .86n2t/4sinn = .15, which yields t = 160.30 sec.
n
4
To obtain the answer in the text, the first two terms of the sum must be used, which requires an equation solver to solve for t. Note that this reduces t by only .01 seconds.
12a. Since the B.C. are ux(0,t) = ux(L,t) = 0, t > 0, the
solution u(x,t) is given by Eq.(35) with the coefficients cn determined by Eq.(37). Substituting the I.C. u(x,0) = f(x) = sin(nx/L) into Eq.(37) yields
c0 = (2/L)
cn = (2/L)
= (1/L)
Jsin(nx/L)dx = 4/n and Jsin(nx/L)cos(nnx/L)dx
{sin[(n+1)nx/L] - sin[(n-1)nx/L]}dx
(1/n){[1 - cos(n+1)n]/(n+1) - [1 - cos(n-1) n]/(n-1)}
0, n odd; = -4/(n2-1) n, n even. Thus
u(x,t)
2/n-(4/n) exp[-4n2n2a2t/L2]cos(2nnx/L)/(4n2-1)
n=1
where we are now summing over even terms by setting n = 2n.
12b. As t ro we see that all terms in the series decay to zero except the constant term, 2/n. Hence 2/n.
Previous << 1 .. 489 490 491 492 493 494 < 495 > 496 497 498 499 500 501 .. 609 >> Next